Pengaruh Direktur Perempuan Terhadap Agency Cost dan Management Disscussion and Analysis Sebagai Variabel Moderasi - Masthuroh Masthuroh; Nurohmayni Putri; Siti Rahmiati (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study examines the influence of female directors on agency costs, which is an important issue in corporate governance. And Management Discussion and Analysis as moderator. Female directors on agency costs. Using a sample of manufacturing companies registered in Indonesia in 2019-2021. In this study, it was measured using regression. Our findings provide evidence that the appointment of female directors can improve corporate governance, but does not affect or reduce agency costs. Meanwhile, the Management Discussion and Analysis variable is not able to moderate or strengthen the influence of the female director variable on agency costs, so that in further research we can add other variables related to corporate governance.